2018
DOI: 10.1002/mmce.21408
|View full text |Cite
|
Sign up to set email alerts
|

Wideband beam-steerable configuration of metasurface loaded slot antenna

Abstract: In this article, a wideband two dimensional (2D) beam‐steerable antenna structure is presented. The proposed structure is based on a radially gradient hybrid metasurface (RGHMS) illuminated through a slot antenna. The half aperture of the RGHMS comprises of a gradient phase profile topology, while its other half aperture consists of a constant phase profile configuration. The slot antenna possessing the bidirectional radiation pattern is printed on a relatively thin substrate, which operates over a wide bandwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…For showing the potential of the proposed beam steering configuration in the real scenario, the measurement is carried out while considering one of the SCRGMs with slot antenna. In summary, as compared to the previous work, the proposed antenna configuration is more compact and is providing large range for elevation beam scanning in both of the upper and the lower hemispheres of the slot antenna, which is the first structure of its kind. The proposed antenna is designed to operate in the frequency range starting from 9.3 to 9.85 GHz.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…For showing the potential of the proposed beam steering configuration in the real scenario, the measurement is carried out while considering one of the SCRGMs with slot antenna. In summary, as compared to the previous work, the proposed antenna configuration is more compact and is providing large range for elevation beam scanning in both of the upper and the lower hemispheres of the slot antenna, which is the first structure of its kind. The proposed antenna is designed to operate in the frequency range starting from 9.3 to 9.85 GHz.…”
Section: Introductionmentioning
confidence: 87%
“…The main emphasis in refs. was to achieve beam steering in both azimuth and elevation planes, which basically requires quite rotationally symmetric phase distribution of the corresponding electric field component. It was observed that at an approximate height of 0.50 λ 0 from the aperture of the antenna, the nonzero E y component shows quite rotationally symmetric phase distribution for this configuration as clearly seen in Figure A.…”
Section: Configuration Evolutionmentioning
confidence: 99%
See 3 more Smart Citations